Correlation and Comparative Evaluation of MOCART and MOCART 2.0 for Assessing Cartilage Repair - Felix Conrad Oettl; Louis Leuthard; Moritz Brunner; Vincent A. Stadelmann; Stefan Preiss; Michael Leunig; Gian M. Salzmann; Jakob Hax (Medicina)
Background and Objectives: Chondral and osteochondral lesions can lead to osteoarthritis if untreated, making accurate assessment of cartilage repair outcomes essential for optimizing treatment strategies. The objective of this study was to compare MOCART and MOCART 2.0 and to evaluate the clinical utility of both across different surgical cartilage repair techniques and various time points. Material and Methods: This study included 111 patients (age: 35 ± 10, 35% female) who underwent cartilage repair surgery of the knee between September 2015 and March 2022. A total of 188 postoperative magnetic resonance images were evaluated using MOCART and MOCART 2.0. The correlations between both scores, as well as to the change in Patient-Reported Outcome Measures (PROMs), were determined. Results: MOCART 2.0 scores (66 ± 13) were significantly higher than MOCART scores (58 ± 13, p < 0.001). Positive correlation was observed between scoring systems (r = 0.837, p < 0.001). There was no significant correlation between MOCART or MOCART 2.0 scores and the change in PROMs. Noticeably, there was a statistically significant correlation between both MOCART and MOCART 2.0 in the AutoCart subgroup across multiple timepoints for the change in PROMs. Conclusions: Based on radiographic–clinical outcome discordance, clinicians should not rely solely on MOCART or MOCART 2.0 scores when evaluating cartilage repair success but instead prioritize patient-reported functional improvements while using imaging as a complementary assessment tool.